Crank-Nicolson time-marching. - Giles, M (Oxford-Man Institute of Quantitative Finance, 2008)
This entry describes the Crank-Nicolson time-marching discretisation and its numerical properties. It also presents the Rannacher startup procedure which is required to achieve second order accuracy for the option value and its first and second derivatives, and discusses extensions to nonlinear and multi-factor applications.